2008
DOI: 10.1007/s10816-008-9052-x
|View full text |Cite
|
Sign up to set email alerts
|

The Bioarchaeological Investigation of Childhood and Social Age: Problems and Prospects

Abstract: Recently, the value of the study of children and childhood from archaeological contexts has become more recognized. Childhood is both a biological and a social phenomenon. However, because of specialization in research fields within anthropology, subadults from the archaeological record are usually studied from the biological perspective (bioarchaeology) or, more predominantly, the social perspective (social archaeology), with little research that incorporates both approaches. These polarized approaches to chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(60 citation statements)
references
References 96 publications
(85 reference statements)
0
59
0
1
Order By: Relevance
“…Dental growth is recognized to be less influenced by environmental factors than by genetics (Halcrow & Tayles, 2008;Saunders et al, 2000;Scheuer & Black, 2000a). However, it has been demonstrated that dental health is partly conditioned by the differential enamel susceptibility of environmental attack (sugars, bacterial flora, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Dental growth is recognized to be less influenced by environmental factors than by genetics (Halcrow & Tayles, 2008;Saunders et al, 2000;Scheuer & Black, 2000a). However, it has been demonstrated that dental health is partly conditioned by the differential enamel susceptibility of environmental attack (sugars, bacterial flora, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Environmental and socio-cultural risks, such as contaminated water, poor sanitation, indoor air pollution, poor food hygiene, poor quality housing, inadequate waste disposal, vector-borne diseases and hazards that cause accidents and injuries, have always endangered children's health (Pronczuk-Garbino 2005). Importantly, in prehistoric and historical societies practically no effective disease treatment could have been offered, especially in the absence of infection control with antibiotics (Halcrow and Tayles 2008). Since vulnerability is the degree to which an individual is unable to cope with, resist and recover from the impacts of adverse factors, subadult health and survival have been accepted as a general measure of the level to which the population has adapted to its environment (Eveleth and Tanner 1990;Lewis 2007).…”
Section: Bioarchaeological Investigations Of Children -Methodologicalmentioning
confidence: 99%
“…It is recommended to focus on subadults as non-survivors and age-structured comparisons of health data, the more so that their age at death is more accurately and precisely assessed than in adults (DeWitte and Stojanowski 2015). Infants and children seem then to be the crucial age subgroups in a population to reconstruct past health and disease (Goodman and Armelagos 1989;Buikstra and Ubelaker 1994;Halcrow and Tayles 2008;Halcrow and Ward 2017), and, more generally, to show the degree to which a population had successfully adapted to its environment, which have been repeatedly demonstrated in bioarchaeological studies (such as Goodman and Armelagos 1989;Ribot and Roberts 1996;Mays 1999;Buckley 2000;Humphrey 2000;Saunders 2000;Lewis 2002;. Two groups of stressors that are most often discussed in relation to growth and health status in past populations are infection and nutrition.…”
Section: Bioarchaeological Investigations Of Children -Methodologicalmentioning
confidence: 99%
“…Gowland 2001Gowland , 2006Sofaer 2006;Halcrow and Tayles 2008;Newman and Gowland 2015;Agarwal 2016). The profound impact of cultural practices on the health and well-being of children is important to consider, but this must be integrated within an understanding of social age transitions and the interplay between age and other aspects of social identity (Gowland 2006).…”
Section: The Social Bioarchaeology Of the Childmentioning
confidence: 99%
“…Childhood diet and the weaning process have important implications for early and later life health, mortality patterns and fertility in past societies (StuartMacadam and Dettwyler 1995;Lewis 2007;Halcrow and Tayles 2008). There is also a synergistic relationship between diet and infection, with poor diet making a person more susceptable to infection, and infection leading to poor nutrient absorption (Lewis 2007).…”
Section: Diet In Infants and Children In The Pastmentioning
confidence: 99%